2019
DOI: 10.1002/prot.25783
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance solution structure of Pisum sativum defensin 2 provides evidence for the presence of hydrophobic surface‐clusters

Abstract: Pisum sativum defensin 2 (Psd2) is a small (4.7 kDa) antifungal peptide whose structure is held together by four conserved disulfide bridges. Psd2 shares the cysteine‐stabilized alpha‐beta (CSαβ) fold, which lacks a regular hydrophobic core. All hydrophobic residues are exposed to the surface, except for leucine 6. They are clustered in the surface formed by two loops, between β1 and α‐helix and β2 and β3 sheets. The observation of surface hydrophobic clusters reveals a remarkable evolution of the CSαβ fold to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…In fact, it has been proposed that disulfide bonds and polar contacts are the main forces responsible for defensin CSαβ folding stability, enabling the surface exposure of hydrophobic residues [74]. Recently, we showed that this was also valid for Psd2, a pea defensin that shares 42% identity and high 3D structural homology with Psd1 [6]. All hydrophobic residues are exposed on the surface, except for Leu6.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In fact, it has been proposed that disulfide bonds and polar contacts are the main forces responsible for defensin CSαβ folding stability, enabling the surface exposure of hydrophobic residues [74]. Recently, we showed that this was also valid for Psd2, a pea defensin that shares 42% identity and high 3D structural homology with Psd1 [6]. All hydrophobic residues are exposed on the surface, except for Leu6.…”
Section: Discussionmentioning
confidence: 61%
“…They display low primary sequence homology, apart from the cysteine residues that are common, two glycine residues (positions 12 and 33), and aromatic residues (positions 10 and 41) related to Psd1 [4,5]. Nevertheless, the tertiary structures of PDs show a common cysteine stabilized αβ-fold (CSαβ-fold), characterized by one α-helix and three antiparallel β-sheets [1,6,7]. Because of their amphipathic characteristics, their ability to kill microorganisms can involve nonspecific electrostatic and hydrophobic interactions with positive plasmatic membranes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant variability of amino acid sequences, experimental structures of plant defensins display high similarity as monomers, suggesting that this fold is important for their biological activity. All structures, except for pea defensin Psd2 [ 50 ], can be superimposed within less than 3Å for Cα atoms of secondary structure motifs, with the majority of structures displaying less than 2Å deviation.…”
Section: Secondary and Tertiary Structuresmentioning
confidence: 99%
“…The role of protein dynamics in the functional activity of plant defensins is suggested by the fact that many functionally important residues are located in the loops [ 60 , 126 ]. Currently, the information on the dynamics of plant defensins comes mostly from NMR relaxation studies, which report that both the picosecond to the nanosecond and the microsecond to millisecond motions are present in plant defensins [ 47 , 48 , 50 , 51 , 60 , 108 , 126 ]. Note that in proteins the microsecond to millisecond motions are typically marked as the most functionally relevant [ 127 , 128 , 129 , 130 , 131 ].…”
Section: Dynamics Properties Of Plant Defensinsmentioning
confidence: 99%
See 1 more Smart Citation